Development and Evaluation of an International Service Learning Program for Nursing Students. Issue 6 (29th April 2013) - Curtin, Alicia J.; Martins, Diane C.; Schwartz‐Barcott, Donna; DiMaria, Lisa; Ogando, Béliga Milagros Soler
Abstract Objectives (1) Using Riner's framework, the development of an international service learning program in the Dominican Republic (DR) for Baccalaureate nursing students will be described, and (2) an initial impact of the students' experiences will be examined. Design and Sample A qualitative descriptive research design was used to examine its impact. The international service learning program included (1) didactic (five, 2 hr and one full day educational sessions) prior to (2) immersion (2 weeks in country), and (3) posttrip debriefing session. Ten females, senior nursing students participated in the program. Students' daily journals were examined using thematic analysis. Results Five major themes that emerged were as follows adapting physically, encountering frustration in their inability to fully meet patients' needs, increasing confidence in speaking Spanish and assessing health problems, and increasing cultural awareness. Students were descriptive regarding their daily activities, and did some, but limited, critical reflection. Conclusions Models of reflection need to be explored to select the most appropriate technique to facilitate students' critical reflection in meeting the goals and objectives of the experience. Curriculum integration of global learning, social consciousness, and global cultural competence development is needed.